Effectiveness of Toll Road and Railway Infrastructure Development in Indonesia - Samsuddin, M. Afdal; Putra, Agung Rizki (AFEBI Economic and Finance Review, 2022)
The purpose of this study is to analyze the effectiveness of toll roads and railways on welfare in Indonesia from the first quarter of 2006 to the fourth quarter of 2020. Toll roads are measured by the length of toll roads, railway lines are measured by the number of train passengers, and welfare is measured by GDP. per capita based on constant 2010 prices. Data analysis techniques use Vector Auto Regressive (VAR), Impulse Response Function (IRF), and Variance Decomposition (VD). The results show that toll roads are much more effective than railways in Indonesia during the study period.